2017
DOI: 10.5301/jva.5000749
|View full text |Cite
|
Sign up to set email alerts
|

Central venous pressure monitoring via peripherally or centrally inserted central catheters: a systematic review and meta-analysis

Abstract: Available evidence supports that CVP monitoring with PICCs is accurate and reproduces similar values to those obtained from CICCs. The possibility to monitor CVP should not be used among clinical criteria for preferring a CICC over a PICC line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The dependence of the bias we measured on the dynamic characteristics of the catheter used (i.e., resistance to bolus injection) is indirectly supported by the fact that in our study the CVP, which is a static pressure measured in no-flow conditions, was unaffected by the type of catheter used, as shown previously [1][2][3][4][5][6]8].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The dependence of the bias we measured on the dynamic characteristics of the catheter used (i.e., resistance to bolus injection) is indirectly supported by the fact that in our study the CVP, which is a static pressure measured in no-flow conditions, was unaffected by the type of catheter used, as shown previously [1][2][3][4][5][6]8].…”
Section: Discussionsupporting
confidence: 83%
“…Several studies demonstrated that PICCs are equivalent to centrally inserted catheters (CICCs) for central venous pressure (CVP) measurement [1][2][3][4][5][6] but there is no evidence they can replace CICCs for cardiac output measurement using TPTD.…”
Section: Introductionmentioning
confidence: 99%
“…We think that the ideal central VAD in this situation is a power injectable peripherally inserted central catheter (PICC), either 5Fr double lumen or 6Fr triple lumen. Recent literature has shown that power injectable polyurethane, non-valved PICCs perform as good as centrally inserted central catheters (CICCs) in intensive care unit; 3,4 in particular, they tolerate very high flow of infusion, they are appropriate for measurement of central venous pressure 5 and for measurement of the cardiac output by thermodilution. 6,7 The risk of thrombosis and infection is similar to CICCs and—for both devices—depends mainly on the insertion technique.…”
Section: Wise Choice Of the Central Vadmentioning
confidence: 99%
“…8,9 The most reliable and broadly used method to assess the CVP is the direct catheterization of the IJV or subclavian veins. 10 However, this is an invasive maneuver with an associated risk of complications and thus is not considered feasible as a routine approach. 11 Recently, it has been shown that the JVP can be obtained using B-mode ultrasound (US) assessment of changes in the cross-sectional area (CSA) of the IJVs over the CC.…”
Section: Introductionmentioning
confidence: 99%